Cloud-based e-government (CBEG): a systematic literature review - Alkhilani, Wissam H. S.; Atan, Rodziah; Abdullah, Salfarina; Jusoh, Yusmadi Yah (College of Science, University of Baghdad, 2024)
The field of cloud-based electronic government (CBEG) is still expanding. Some conflicting results have been published regarding the factors influencing the adoption of CBEG. The paper aims to review the literature and understand the status of CBEG and the factors behind its adoption. Specific keywords related to the topic were used to extract articles from reliable databases. An extensive review was done on a total of 41 articles published between 2016 and August 2022. The findings showed that there has been an increase in the number of articles related to CBEG, specifically in the public sector. The review also showed that the quantitative approach outperformed other approaches. The Technology Organization Environment (TOE) framework and Diffusion of Innovation (DOI) were used in the majority of the reviewed papers. Structural equation modeling (SEM) was applied intensively in the reviewed papers. The most important factors for CBEG adoption are top-level management support, security, compatibility, relative advantage, complexity, and privacy. Future studies are recommended to expand the scope of inclusion criteria, conduct more empirical studies on CBEG, and deploy mediators and moderators. Empirically, combining more theories can explain more about the adoption of CBEG. The findings help decision-makers better understand the predictors of the successful adoption of CBEG.